The staying power of intercultural learning through reflective inquiry. Issue 1 (2nd January 2016) - Wilbur, Gretchen
Abstract: This paper focuses on the staying power of intercultural knowledge, skills and attitudes for adult students who were engaged in reflective inquiry during a travel course. It addresses a need to assess whether new learning gained from reflection on experience persists over time and what factors may influence staying power. The main finding of the study is that intercultural competence developed through reflective inquiry is maintained and often deepened over time. This builds upon previous findings that skills and characteristics of effective intercultural interaction are advanced through using reflective inquiry to analyze observations and resolve puzzling problems triggered by uncertainty. The context for this qualitative inquiry is with undergraduate adult students participating in a travel course designed to develop intercultural competence. They responded to reflective prompts throughout the course and 18 months after completion. Cases are presented that analyze course and post-course responses. I conclude that the intersection of reflective inquiry and intercultural competence frameworks can influence the ongoing persistence of learning over time.